The fiscal and macroeconomic effects of fiscal rules - Lehtimäki, Jonne (Springer Nature, 2025)
A majority of advanced and developing countries have adopted fiscal rules, which aim on managing fiscal aspects, such as government debt, government budget balances and other factors. Alongside national fiscal rules, many economic and monetary unions have implemented common fiscal rules, which affect all member countries and aim on controlling their fiscal aspects in a common way to address potential spillover effects from negative fiscal shocks and provide a more stable macro-fiscal environment. This study uses a fixed effect panel approach on a sample of 106 countries from 1985 to 2021 to study how national and supranational fiscal rules have affected the development of government debt, government budget balances, public investment and economic growth. The results imply that the effectiveness of different fiscal rules is highly heterogeneous and that supranational fiscal rules substantially outperform national fiscal rules. However, a majority of the effects from national fiscal rules remains unchanged when studied alongside supranational rules, suggesting that these rules act as complements rather than substitutes. The effects of fiscal rules are most significant for the studied fiscal variables, with some additional impacts observed for public investment and economic growth.